Association Between Health Anthropometric Indexes with Physical Fitness in Physically Active Elderly Women [Asociación Entare Índices Antropométricos de Salud y Condición Física en Mujeres Mayores Físicamente Activas] - Herrera-Valenzuela, T (Instituto Nacional de Salud Publica, 2017)
Objective. To associate health anthropometric indexes with physical fitness of elderly women (EW) who participate in physical exercise workshops. Materials and methods. 272 Chilean women over 60 years took part in the study. The variables studied were BMI, waist circumference (WC), waist-height index (WHI) and physical fitness (PF). Correlations were made through the Pearson or Spearman coefficient, and bivariate associations using Pearson s Chi-square and the Fisher s exact test, considering p < 0.05. Results. 70.8% of the EW were overweight or obese; 68.8% and 96% were at cardiometabolic risk due to their WC and WHI, respectively. Their PF showed equal performance (53.5%) or higher (33.8%) according to their age and gender. Inverse correlations were found between nutritional status and cardiometabolic risk with PF tests (except for agility and dynamic balance [direct]), and direct association with back scratch test. Conclusions. Excess weight in physically active EW would not affect their physical-functional performance; however, cardiometabolic risk would be inversely associated with motor function.